SPECIFIC LEXICAL-GRAMMATICAL FEATURES OF ENGLISH COPULATIVE VERBS - Abdurakhmanova Mokhinur Bahromjon kizi (Лучшие интеллектуальные исследования, 2023)
Annotation: The word copulative is derived from the Latin word "copula" which means "to bind". These verbs connect the possessor to the phrase it expresses, that is, to be more precise, to the complement. Many scientists have recognized that nouns and pronouns are connected in the memory of copulative verbs.